2001
DOI: 10.1073/pnas.111007198
|View full text |Cite
|
Sign up to set email alerts
|

Roles of DNA polymerases V and II in SOS-induced error-prone and error-free repair in Escherichia coli

Abstract: DNA polymerase V, composed of a heterotrimer of the DNA damage-inducible UmuC and UmuD 2 proteins, working in conjunction with RecA, single-stranded DNA (ssDNA)-binding protein (SSB), ␤ sliding clamp, and ␥ clamp loading complex, are responsible for most SOS lesion-targeted mutations in Escherichia coli, by catalyzing translesion synthesis (TLS). DNA polymerase II, the product of the damage-inducible polB (dinA ) gene plays a pivotal role in replication-restart, a process that bypasses DNA damage in an error-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 56 publications
(98 reference statements)
3
52
1
Order By: Relevance
“…These misincorporation rates are 100 -1000-fold higher than those reported for replicative polymerases, such as ␣ subunit from E. coli (10 Ϫ4 to 10 Ϫ5 ) (21). These rates are also higher than those reported for errorfree repair polymerases, such as Pol II (misincorporation efficiency ϳ10 Ϫ4 ) (22)(23)(24). Fig.…”
Section: S Pyogenes Dnae Is a Low Fidelitycontrasting
confidence: 40%
“…These misincorporation rates are 100 -1000-fold higher than those reported for replicative polymerases, such as ␣ subunit from E. coli (10 Ϫ4 to 10 Ϫ5 ) (21). These rates are also higher than those reported for errorfree repair polymerases, such as Pol II (misincorporation efficiency ϳ10 Ϫ4 ) (22)(23)(24). Fig.…”
Section: S Pyogenes Dnae Is a Low Fidelitycontrasting
confidence: 40%
“…Four of the recA genes are located on four separate plasmids (pREB1, -2, -4, and -5), and the other three are on the main chromosome. Multiple copies of umuD (4x) and umuC (3x), two sets of which are plasmid-encoded, and two putative proteins with a lambda-phage cI motif are also likely correlated with the extra recA (22,24). The presence of multiples copies of recA and related enzymes could account for gene duplication and/or integration of foreign genes that would lead to genome expansion.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, cell lysis could be counterproductive in multispecies environments as it would provide the other species with a selective advantage and supply them with additional resources. Such ecological differences may explain why Caulobacter cells undergo apoptotic-like death whereas other species have evolved the lesion bypass pathway in which they excise and replace irreparably damaged DNA with an errorprone polymerase (6,24), trading off cell survival for the cost of passing on dramatically altered genomes. Further support for the analogy between the damage responses of Caulobacter and multicellular eukaryotes comes from the fact that both systems promote cell death by inducing chromosome fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we focus on the DNA damage response of Caulobacter crescentus because it lacks known lesion bypass pathways for copying extremely damaged DNA (6) and it has a eukaryotic-like cell cycle in which it replicates its DNA once and only once per cell division (7). Although the DNA damage response is less well characterized in Caulobacter than in other bacteria such as E. coli (8), a recent study identified SidA as an early SOS-induced division inhibitor in C. crescentus (9).…”
mentioning
confidence: 99%